Comparative Analysis and Design of PublicBuilding Using Manual Method and STAAD.ProSoftware (International Journal of Communication Systems and Network Technologies, 2023)
Analysis and design of a any building needs basic knowledge of structural analysis, so in this project considering basic idealization how the structure is to analyze and design is to be carry out is covered by considering some ongoing projects. In the project tried to cover all the necessary analysis data consideration for different loads and load combination is considered manually and results are compared with software readings by considering same and design data loads and load combination. In detailed detailing is also tried to cover as per the IS code provisions.
Keywords: Structural Analysis; STAAD.Pro; Manual Design; Load Calculation; IS 456:2000; Reinforced Concrete